General geology and petrology of plutonic rocks in Kg. Lata Janggut, Jeli, Kelantan - Athirah Rosli (2022)
The study area is located at Kg. Lata Janggut, Jeli, Kelantan with an area of 25 km2. The objectives of this study are to produce the geological map of the study area with a scale of 1:25000, determine the types of plutonic rocks, and the types of magma and tectonic setting for Kg. Lata Janggut, Jeli, Kelantan. The data used in this study is a secondary data from various resources. For petrology study, petrography analysis was conducted using hand specimen and thin section to identify minerals present, which could indicate the rock environment. Petrography analysis also supports geochemistry analysis that was conducted on both major and trace elements in investigating magma source and magmatism process in the area. A total of 29 plutonic rocks samples were used and processed using GeoChemical Data ToolKIT (GCDkit) software to identify geotectonic and rock types. The results suggest that the study area was formed by subduction of Sibumasu and Indochina plates. This event is responsible for the presence of volcanic and igneous rock at the area. The rocks in the area are of syn-collision type calc-alkaline granite.